How Product Review, Price and Ease of Transaction Affect Online Purchase Decision: Study of Bukalapak Users in Gelgel Village, Bali - Tjokorda Gde Agung Wijaya Kesuma Suryawan; I Komang Sumerta; Ayu Putu Satya Widiantari; Sharmini Abdullah (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
This research is based on gaps in previous research findings (research gaps) and compares discussion priorities and purchasing decisions on product reviews, price, and transaction convenience. Furthermore, the research issue in this study is the lack of incentives acquired by customers to shop on Bukalapak e-commerce, as customers sometimes receive items that do not match their orders, deliveries do not arrive on time, as well as customers often encounter problems with shopping online on Bukalapak e-commerce. This study focused on Bukalapak e-commerce customers in Gelgel Village, Bali. The 82 respondents were obtained using a purposive random sampling method. All information obtained from the questionnaire distribution was suitable for use and then analyzed using multiple linear regression analysis and hypothetical tests (t-Test and f-Test). The research proved that product reviews positively and significantly affected purchasing decisions. Prices had a partially positive and significant impact on purchasing decisions. Also, ease of transaction positively and significantly affected purchasing decisions. Subsequently, product reviews, price and transaction ease simultaneously had positive and significant effects on the purchase decisions of Bukalapak customers of Gelgel Village, Bali. The critical analysis presented in this paper holds the potential to contribute to the academic community in the field of marketing. Specifically, it offers valuable insights for researchers exploring the utilization of online commerce, shedding light on untapped research opportunities and uncovering previously undiscovered signals. Furthermore, it paves the way for developing diverse and innovative studies to enrich this domain’s scholarly discourse.